Morphology of the feeding apparatus of cave shrimps of the genus Typhlatya (Decapoda: Atyidae) from the Yucatán Peninsula and comparison with epigean species - Ivonne Trejo-Ventura; Gema Armendáriz; José Luis Villalobos; Fernando Álvarez (Revista Mexicana de Biodiversidad)
The setal arrangement on the dactyl and propodus of pereopods 1 and 2, defined here as the feeding apparatus, of 3 species of cave shrimps of the genus Typhlatya (T. mitchelli, T. pearsei, T. dzilamensis) from the Yucatán Peninsula was studied using SEM micrographs. The setae were classified according to their morphology and position in the propodus and dactyl resulting in 6 main types. The 3 Typhlatya species differed slightly in the number of each type of setae and showed some morphological variations, especially in the central setae. A comparison of the setal arrangement of Typhlatya spp. with that of the epigean Potimirim mexicana and P. glabra, showed important differences probably driven by the specialization to specific habitats.